2019
DOI: 10.1177/2309499019859838
|View full text |Cite
|
Sign up to set email alerts
|

Posterior wall acetabular fracture fixation: A mechanical analysis of fixation methods

Abstract: Stable, anatomical fixation of acetabular fractures gives the best chance of successful outcome, while penetration of the acetabular articular surface with screws is associated with poor outcomes. Spring plates are an alternative to interfragmentary lag screws when penetration is a concern. A mechanical study comparing fracture stability and construct stiffness of three fixation methods for posterior wall acetabular fractures with transverse comminutions was performed. The three fixation methods tested were a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…For biomechanical tests, research groups could choose between human cadaveric pelves prepared in various ways, or synthetic pelvis models, which consisted of bone substitutes intended to reflect the biomechanics of physiological bone. Most research groups investigating fixation methods for acetabular fractures used synthetic pelves models (25 test setups) [ 28 32 , 35 44 , 49 51 , 54 56 , 60 63 ]. These models consisted of a whole pelvis or a hemipelvis model fixed in different ways to enable particular loading directions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For biomechanical tests, research groups could choose between human cadaveric pelves prepared in various ways, or synthetic pelvis models, which consisted of bone substitutes intended to reflect the biomechanics of physiological bone. Most research groups investigating fixation methods for acetabular fractures used synthetic pelves models (25 test setups) [ 28 32 , 35 44 , 49 51 , 54 56 , 60 63 ]. These models consisted of a whole pelvis or a hemipelvis model fixed in different ways to enable particular loading directions.…”
Section: Resultsmentioning
confidence: 99%
“…Pease et al mounted a synthetic pelvis so that the anterior superior iliac spine and symphysis pubis were vertical, and the joint surface of the symphysis was vertical at 90° to this plane. Additionally, flexion of the pelvis in the hip joint was simulated with the pelvis loaded axially by an artificial femoral head [ 54 ]. Olson et al used a single-leg stance protocol, in which a linear actuator applied the loading force via a simulated abductor mechanism to a cadaveric pelvis rigidly mounted at the sacrum and moveably connected to the femur [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 35% of acetabular fractures, the posterior wall had been involved, being is the most common affected, with about 76% of these injuries had complex fractures [2] .…”
Section: Introductionmentioning
confidence: 99%
“…In general, isolated posterior wall fractures are considered to have a good prognosis, but recent reviews have shown that 21% and 32% of patients have a poor prognosis [2] .…”
Section: Introductionmentioning
confidence: 99%